2013
DOI: 10.1016/j.diii.2013.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound elastography in liver

Abstract: Conventional imaging techniques cannot provide information about tissue mechanical properties. Many injuries can cause changes in tissue stiffness, especially tumors and fibrosis. In recent years, various non-invasive ultrasound methods have been developed to study tissue elasticity for a large number of applications (breast, thyroid, prostate, kidneys, blood vessels, liver…). For non-invasive assessment of liver diseases, several ultrasound elastography techniques have been investigated: Transient elastograph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
141
0
7

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 173 publications
(152 citation statements)
references
References 83 publications
4
141
0
7
Order By: Relevance
“…SWE revealed that malignant tissues of breast lesions have higher stiffness due to the increase in the number of malignant cells and surrounding desmoplas- tic reactions (8). Several studies have evaluated noninvasive elastographic techniques for assessing liver fibrosis, which may decrease the need for liver biopsy (9). Other organ systems such as the hormone secretion system and the musculoskeletal system (10) have also been investigated.…”
Section: Discussionmentioning
confidence: 99%
“…SWE revealed that malignant tissues of breast lesions have higher stiffness due to the increase in the number of malignant cells and surrounding desmoplas- tic reactions (8). Several studies have evaluated noninvasive elastographic techniques for assessing liver fibrosis, which may decrease the need for liver biopsy (9). Other organ systems such as the hormone secretion system and the musculoskeletal system (10) have also been investigated.…”
Section: Discussionmentioning
confidence: 99%
“…But there are also some limitations, such as obesity, does not have capability to present data in ascites mediums and in focal lesion. The main limitation about liver is the non capability of measurement in left lobe 22,23,[28][29][30][31][32] .…”
Section: (Acoustic Radiation Force Impulse Elastography Shear-wave Ementioning
confidence: 99%
“…Two main types of these methods are used: Analysis of serum biomarkers combinations (e.g., FibroTest) and novel imaging techniques that measure liver stiffness (elasticity), which is reduced in the presence of fibrosis. Elastography techniques include: Transient elastography (FibroScan, which analyzes liver stiffness by measuring the velocity of elastic shear waves generated by a mechanical impulse), Acoustic Radiation Force Impulse imaging (ARFI, method for quantifying mechanical properties of liver tissue by measuring the shear wave velocity which is induced by acoustic radiation), and Shear Wave Elastography (SWE, quantitative real-time assessment, based on the generation of a radiation force in the tissue in order to create the shear wave) [28,29]. Another method is Magnetic Resonance Elastography, which is expensive and, therefore, has not been used for clinical purposes yet.…”
Section: Discussionmentioning
confidence: 99%